The relationship between service quality and patient satisfaction in internal medicine outpatient care: A cross-sectional study - Brico Alfrian; Silvia Haniwijaya Tjokro; Rina Budi Kristiani; Firnanda Erindia (School of Health Sciences Al-Ma'arif, 2025)
Background: Service quality is a critical determinant of patient satisfaction and plays an essential role in shaping patient experiences in outpatient care settings. Ensuring high-quality services is a priority for hospitals, particularly in internal medicine clinics where patient volumes and clinical needs are substantial. Objective: This study aimed to analyze the relationship between healthcare service quality and patient satisfaction among outpatients at the Internal Medicine Clinic of Husada Utama Hospital Surabaya. Methods: This cross-sectional quantitative study involved 49 respondents selected through probability sampling from a total outpatient population of 24,262 visits. Data were collected using structured questionnaires, interviews, observations, and documentation, and were analyzed using descriptive statistics and Spearman’s rank correlation with a significance level of p < 0.05. Results: Most respondents perceived service quality as adequate (67.3%) and reported patient satisfaction at an adequate level as well (61.2%). The Spearman correlation test indicated a moderate, positive, and significant association between service quality and patient satisfaction (ρ = 0.632, p = 0.000), suggesting that higher service quality contributed to increased satisfaction. Conclusion: Service quality demonstrated a significant contribution to patient satisfaction in the Internal Medicine Clinic, highlighting the need for continuous improvement in service responsiveness, empathy, reliability, and physical facilities. The hospital is encouraged to enhance communication skills among staff, streamline service processes, optimize waiting room facilities, and implement regular evaluation mechanisms to strengthen patient-centered care and sustain long-term patient trust.